IMPLEMENTASI APLIKASI TEMAN BISNIS DALAM DIGITALISASI KEUANGAN PADA WARUNG BAKSO & MIE AYAM OJO LALI SEBAGAI UPAYA PENINGKATAN EFISIENSI PENGELOLAAN KEUANGAN - Dhea Febriyani; Muhamad Reza Muhfi; Novita Fitri Syabila; Riska Herdiana; Sylvia Febriyani; Hamdy Febrian; Prisila Damayanty; Zara Tania Rahmadi; Indra Setiawan (ASOSIASI IDEBAHASA KEPRI, 2026)
This Community Service Program (PKM) aims to improve financial management efficiency in the MSME “Warung Bakso & Mie Ayam Ojo Lali” through the implementation of the Teman Bisnis application as a financial digitalization effort. The problems faced by the partner include manual transaction recording, unstructured bookkeeping, and limitations in preparing accurate financial reports. This study is based on various studies and community service activities conducted by researchers from Institut Bisnis dan Informatika (IBI) Kosgoro 1957, which indicate that the utilization of digital technology can improve the quality of MSME financial management. The implementation methods include observation, socialization, training, and assistance in using the Teman Bisnis application. The results show that the implementation of the Teman Bisnis application helps business owners record financial transactions in a more organized, systematic, and real-time manner. In addition, partners gain a better understanding of their financial condition, enabling them to make more appropriate business decisions. Therefore, financial digitalization through this application is expected to enhance efficiency and sustainability of Warung Bakso & Mie Ayam Ojo Lali’s business.